2014
DOI: 10.1093/ejcts/ezu319
|View full text |Cite
|
Sign up to set email alerts
|

Bicuspid aortic valve: phosphorylation of c-Kit and downstream targets are prognostic for future aortopathy

Abstract: Using a panel of molecular tissue markers, the non-dilated BAV patients can be divided into groups susceptible and non-susceptible to aortopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 20 publications
5
47
0
Order By: Relevance
“…Even though we did not measure reactive oxygen species production, we found no difference in the expression of their scavenger enzymes heme oxygenase and glutathione peroxidase. So far, all of these facts indicate a very finely tuned inflammatory process in human aortic aneurysms and therefore the recently postulated prognostic value for phosphorylation of c-kit and downstream targets in aneurysm formation fits well in this concept [20]. In this context, recent studies reported that the inhibition of cytokine IL-1 attenuates experimental development of aortic aneurysm [21], as well as activation of TGF-signalling [22].…”
Section: Discussionmentioning
confidence: 68%
“…Even though we did not measure reactive oxygen species production, we found no difference in the expression of their scavenger enzymes heme oxygenase and glutathione peroxidase. So far, all of these facts indicate a very finely tuned inflammatory process in human aortic aneurysms and therefore the recently postulated prognostic value for phosphorylation of c-kit and downstream targets in aneurysm formation fits well in this concept [20]. In this context, recent studies reported that the inhibition of cytokine IL-1 attenuates experimental development of aortic aneurysm [21], as well as activation of TGF-signalling [22].…”
Section: Discussionmentioning
confidence: 68%
“…The decreased TGF-β signaling could impair the expression of MYOCD and thus down regulate SMC marker gene expression, including MYH11 . Interestingly, two groups have reported separately that impaired canonical TGF-β signaling was also found in the ascending aortic tissue in BAV patients, and might potentiate the development of aneurysms in BAV (Grewal et al, 2014a, Paloschi et al, 2015). Our in vitro model provided another piece of evidence that defective TGF-β signaling might be the cause of the defective differentiation of NCSCs and the observed aortopathy in the BAV patients with ascending aortic aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…We all have been educated by the elegant and seminal work of Leonardo Da Vinci, suggesting that a semilunar valve carrying three cusps is more efficient compared to a bicuspid valve. However, in the human a bicuspid valve is the most common congenital heart “malformation,” often going undetected until later in adult life and then usually associated with aortic aneurysm . Recent investigations using transgenic mice demonstrated that mutated “OFT genes” (NOTCH, eNOS, GATA4/5, NKx2.5, and TGFβ pathway, compiled by DeWaard and Postma) are associated with bicuspidy, most likely by disturbed SHF addition and neural crest disturbances.…”
Section: Evo‐devo Aspects Of Congenital Malformationsmentioning
confidence: 99%
“…However, in the human a bicuspid valve is the most common congenital heart "malformation," often going undetected until later in adult life and then usually associated with aortic aneurysm. 143 Recent investigations using transgenic mice demonstrated that mutated "OFT genes" (NOTCH, eNOS, GATA4/5, NKx2.5, and TGFβ pathway, compiled by DeWaard and Postma 225 ) are associated with bicuspidy, most likely by disturbed SHF addition and neural crest disturbances. Considering reptiles, we know that these animals usually have bicuspid valves in their three OFT vessels and seem not to be encumbered by this situation.…”
Section: Bicuspid Semilunar Valvesmentioning
confidence: 99%